The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jhep.2015.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of distal cholesterol biosynthesis in association with relapse and advanced disease in CHC genotype 2 and 3 treated with sofosbuvir and ribavirin

Abstract: BACKGROUND AND AIMS: Hepatitis C virus (HCV) modulates host lipid metabolism for its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…One possible hypothesis is that the metabolism of DAAs may be different among patients with different genotypes. Recently, Younossi et al 19 assessed the cholesterol pathway in patients with HCV genotypes 2 and 3 and found that the presence of HCV genotype 3 was associated with reduced circulation of lipids, resulting in relative hypocholesterolemia, a possible basis for the hampered virologic response with this genotype. Whether this same pathway also could be involved in increasing the risk of adverse events requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…One possible hypothesis is that the metabolism of DAAs may be different among patients with different genotypes. Recently, Younossi et al 19 assessed the cholesterol pathway in patients with HCV genotypes 2 and 3 and found that the presence of HCV genotype 3 was associated with reduced circulation of lipids, resulting in relative hypocholesterolemia, a possible basis for the hampered virologic response with this genotype. Whether this same pathway also could be involved in increasing the risk of adverse events requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that specific HCV core protein polymorphisms are associated with intrahepatic lipid accumulation in HCV-3a, providing further evidence for viral and genotype specific steatosis [39]. Also, HCV-3 appears to selectively disrupt de novo lipogenesis in the distal cholesterol biosynthesis pathway [40], with restoration of distal lipid metabolites following successful DAA therapy [41]. This is in keeping with observed restoration in total cholesterol and apoB levels following viral clearance[42].…”
Section: Hcv Genotype 3 Infection and Steatosismentioning
confidence: 99%
“…Additionally, reduced serum VLDL-TG level is a marker of chronic hepatitis C in the early stage of fibrotic disease 31. In response to IFN-free DAA treatment, serum TG level,32 VLDL particle size,32 apoAII and apoE33 levels decrease, while LDL-Chol level32 and LDL particle size32 increase and the distal sterol metabolites are altered in a genotype-dependent manner 34. Currently, the mechanistic and clinical relevance of the normalisation of these lipid components in anti-HCV DAA treatment remains important to determine.…”
Section: Introductionmentioning
confidence: 99%